2019
DOI: 10.1111/gcbb.12585
|View full text |Cite
|
Sign up to set email alerts
|

Cellulosic biofuel crops alter evapotranspiration and drainage fluxes: Direct quantification using automated equilibrium tension lysimeters

Abstract: An increasing number of crops are being considered as potential sources of biomass for both conventional (e.g., maize/corn) and cellulosic (e.g., switchgrass, miscanthus, and hybrid poplar) biofuels. Studies investigating the hydrologic characteristics of these crops are often conducted at either the field scale with a focus on evapotranspiration (ET) or at the plot scale where experiments generally rely on soil water storage dynamics and residual water balances. While this has led to many important insights i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…For example, in nearby sites, Hamilton et al () found similar ET gs rates for switchgrass, restored prairie, and corn. Parish et al () also found similar ET gs rates between switchgrass and corn in the upper US Midwest. In southern Ontario, Canada, Eichelmann, Wagner‐Riddle, Warland, Deen, and Voroney () found lower ET gs rates for switchgrass than for corn.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…For example, in nearby sites, Hamilton et al () found similar ET gs rates for switchgrass, restored prairie, and corn. Parish et al () also found similar ET gs rates between switchgrass and corn in the upper US Midwest. In southern Ontario, Canada, Eichelmann, Wagner‐Riddle, Warland, Deen, and Voroney () found lower ET gs rates for switchgrass than for corn.…”
Section: Discussionmentioning
confidence: 74%
“…There was not much difference in the soil surface and physical conditions between the perennial and corn fields within each land use history in the first 2 years following conversion as the fields had been managed similarly for many years prior. However, the difference in crop types and management from 2013 onwards likely resulted in higher root biomass that add organic matter to the soil (Kong & Six, ; Ruess et al, ) improving soil structure and consequently the infiltration of precipitation (Bonin, Lal, Schmitz, & Wullschleger, ; Zaibon et al, ) into the soil through improved soil surface conditions in the perennial fields (e.g., Parish et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Field studies that have compared ET in annual crops to that of perennial biofuel crops are fairly limited, and the results have been mixed. For well-drained soils, some studies have found that both crop types have similar growing-season ET rates (Abraha et al, 2015;Abraha et al, 2020;Hamilton et al, 2015;Parish et al, 2019), while perennials have higher growing-season ET rates than annual crops in soils with high water tables (Hickman et al, 2010;Zeri et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Field studies that have compared ET in annual crops to that of perennial biofuel crops are fairly limited, and the results have been mixed. For well‐drained soils, some studies have found that both crop types have similar growing‐season ET rates (Abraha et al, 2015; Abraha et al, 2020; Hamilton et al, 2015; Parish et al, 2019), while perennials have higher growing‐season ET rates than annual crops in soils with high water tables (Hickman et al, 2010; Zeri et al, 2013). Similarly, mixed results come from modelling studies, as some show no difference in growing‐season ET rates (Song et al, 2016), while others show higher growing‐season ET rates for perennials than for annuals (Le et al, 2011; Schilling et al, 2008; VanLoocke et al, 2012; Zhuang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%